Extraction of Lysozyme by Hydroxyl-Functionalized Ionic Liquid Aqueous Two-Phase System - Zhou, Bo; Gou, Gaozhang; Xu, Shijuan; Zhang, Pei; Liu, Wei (Asian Journal of Chemistry, 2015)
An ionic liquid/aqueous two-phase system (ATPS) based on the hydroxyl-functionalized ionic liquid 3-(2,3-dihydroxypropyl)-1-methylimidazolium chloride ([2,3-dhpmim]Cl) and salt has been applied directly for extraction of lysozyme. Some effects on the extraction efficiency have been investigated systematically, such as the kind of salts, the amounts of the salt and ionic liquid and the pH of solvent. The results show that ionic liquid-ATPS can be used for extraction of lysozyme efficiently. With the pH value of solution 11.5, the concentration of K3PO4 34 % (mass fraction) and ionic liquid 2.5 mL, ionic liquid-ATPS had the highest extraction efficiency (87 %).